Data from: A hormone-related female anti-aphrodisiac signals temporary infertility and causes sexual abstinence to synchronize parental care - Engel, Katharina C.; Stökl, Johannes; Schweizer, Rebecca; Vogel, Heiko; Ayasse, Manfred; Ruther, Joachim; Steiger, Sandra (Dryad, 2018)
The high energetic demand of parental care requires parents to direct
their resources towards the support of existing offspring rather than
investing into the production of additional young. However, how such a
resource flow is channelled appropriately is poorly understood. In this
study, we provide the first comprehensive analysis of the physiological
mechanisms coordinating parental and mating effort in an insect exhibiting
biparental care. We show a hormone-mediated infertility in female burying
beetles during the time the current offspring is needy and report that
this temporary infertility is communicated via a pheromone to the male
partner, where it inhibits copulation. A shared pathway of hormone and
pheromone system ensures the reliability of the anti-aphrodisiac. Female
infertility and male sexual abstinence provide for the concerted
investment of parental resources into the existing developing young. Our
study thus contributes to our deeper understanding of the mechanisms
underlying adaptive parental decisions.
Daten Engel et al Dryad
Keywords: pheromone; Nicrophorus vespilloides; juvenil hormone; mating